Overtreatment of asymptomatic bacteriuria: a qualitative study. Issue 3 (July 2016) - Eyer, M.M.; Läng, M.; Aujesky, D.; Marschall, J.
Summary: Background: Overtreatment of asymptomatic bacteriuria (ASB) is widespread and may result in antibiotic side-effects, excess costs to the healthcare system, and may potentially trigger antimicrobial resistance. According to international management guidelines, ASB is not an indication for antibiotic treatment (with few exceptions). Aim: To determine reasons for using antibiotics to treat ASB in the absence of a treatment indication. Methods: A qualitative study was conducted at a tertiary care hospital in Switzerland during 2011. We interviewed 21 internal medicine residents and attending physicians selected by purposive sampling, using a semi-structured questionnaire. Responses were analysed in an inductive thematic content approach using dedicated software (MAXQDA ® ). Findings: In the 21 interviews, the following thematic rationales for antibiotic overtreatment of ASB were reported (in order of reporting frequency): (i) treating laboratory findings without taking the clinical picture into account ( N = 17); (ii) psychological factors such as anxiety, overcautiousness, or anticipated positive impact on patient outcomes ( N = 13); (iii) external pressors such as institutional culture, peer pressure, patient expectation, and excessive workload that interferes with proper decision-making ( N = 9); (iv) difficulty with interpreting clinical signs and symptoms ( N = 8). Conclusion: In this qualitative study we identified both physician-centred factors (e.g. overcautiousness) and external pressors (e.g. excessive workload) as motivators for prescribing unnecessary antibiotics. Also, we interpreted the frequently cited practice of treating asymptomatic patients based on laboratory findings alone as lack of awareness of evidence-based best practices.